(untitled) (Journal of Nursing Future Care: AI and Innovation, 2026)
The integration of artificial intelligence (AI) into surgical and nursing environments has significantly improved operational efficiency and patient safety, particularly in emergency operation theaters (EOTs), where rapid decision-making and strict sterility are essential. Smart voice-controlled hands-free assistance systems enable surgeons to interact with medical devices, retrieve patient information, and perform real-time documentation without physical contact, thereby reducing contamination risks and workflow interruptions. These systems utilize advanced technologies such as speech recognition, natural language processing, and machine learning to interpret commands and execute tasks with high accuracy and speed. This article examines the architecture, key applications, advantages, and limitations of AI-enabled voice-controlled systems in emergency surgical settings. It also discusses their role in enhancing clinical decision-making, reducing cognitive workload, and improving coordination among surgical teams. Furthermore, the paper highlights current challenges, including speech recognition accuracy in noisy environments, data privacy concerns, and system integration complexities. Supported by recent literature from the past decade, this study emphasizes the transformative potential of AI-driven surgical assistance systems.